Effect of Liquid Smoke from Pyrolysis of Durian Skin and Etanol Extract of Orange Peel as Bio Hand Sanitizer - Muh Arman; Hijrah Amaliah Azis; Shinta Basri; Faqih Naufal (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2023)
Liquid smoke resulting from pyrolysis of durian skin has antibacterial potential which is used as a basic ingredient for making bio hand sanitizer. Durian skin is difficult to degrade because it contains high levels of lignin, cellulose, and hemicellulose compounds, so with the use of durian skin, it is expert that it will be able to reduce durian skin waste. Bio hand sanitizer is formulated with essential oils to reduce the pungent aroma of smoke. This study aims to determine the antibacterial activity and characteristics of the durian skin liquid smoke bio hand sanitizer. This study used the Completely Randomized Design (CRD) method, with a comparison between durian peel liquid smoke and orange peel extract and the addition of 10 mL NaOH (1:3, 1:1,57, 1:1, and 3:1). The results of research based on characteristic tests obtained pH values of 4.81-7.36, viscosity 1392-3664 cps. Formula E (3:1) emerged as the best sample through organoleptic tests on each bio hand sanitizer preparation formula. It exhibited a yellow color, a runny texture, and a smoky aroma with the mixture. The antibacterial test demonstrated that the bio hand sanitizer preparation possessed antibacterial activity, and the resistance diameter for the test bacteria S. Aureus and E. Coli ranged from 21.51 to 31.14 mm